2020
DOI: 10.1136/bmj.m1731
|View full text |Cite
|
Sign up to set email alerts
|

Interventions supporting long term adherence and decreasing cardiovascular events after myocardial infarction (ISLAND): pragmatic randomised controlled trial

Abstract: Objective To test a scalable health system intervention to improve long term adherence to secondary prevention treatments among patients who have had a recent myocardial infarction. Design Three arm, pragmatic randomised controlled trial with blinded outcome assessment. Setting Nine cardiac centres in Ontario, Canada. Participants 2632 patients with obstructive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 50 publications
(59 reference statements)
1
63
0
2
Order By: Relevance
“…Prior research suggesting that virtual care may be particularly effective for mental health issues may explain the higher use of virtual care in this population. Virtual care has also been shown to improve care for patients with heart failure, 25 chronic obstructive pulmonary disease, 26 , 27 coronary artery disease 28 and diabetes. 29 Further study is required to understand which diseases and conditions are most amenable to virtual care, the optimal dosing of virtual care (frequency of visits, duration) and the content of visits (e.g., symptom assessment, medication reconciliation).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggesting that virtual care may be particularly effective for mental health issues may explain the higher use of virtual care in this population. Virtual care has also been shown to improve care for patients with heart failure, 25 chronic obstructive pulmonary disease, 26 , 27 coronary artery disease 28 and diabetes. 29 Further study is required to understand which diseases and conditions are most amenable to virtual care, the optimal dosing of virtual care (frequency of visits, duration) and the content of visits (e.g., symptom assessment, medication reconciliation).…”
Section: Discussionmentioning
confidence: 99%
“…22 While active forms of education, like cognitive education and behavioural counselling seem to work, 53 more passive forms of education are often unsuccessful at changing behaviour, as in a recent trial where the intervention comprised of a mail and phone education strategy to encourage patients to take prescribed medication had no impact on adherence. 54 Others have found that multifaceted interventions focusing on enhancing care provision through team-based care may be effective at increasing statin adherence. 55 However, when trying to target the problem of low statin prescribing, interventions directed only at patients are not likely to work.…”
Section: Discussionmentioning
confidence: 99%
“…78 Another study sought to assess the impact of mailed information and interactive phone calls on adherence to medication and cardiac rehabilitation programs after an AMI. 79 None of the interventions resulted in significant increases in medication adherence, possibly pointing to the diminished relevance of printed materials.…”
Section: Multi-factor Components: (1) Wearable Device (2) Mobile Appmentioning
confidence: 99%